1997
DOI: 10.1074/jbc.272.43.27324
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression, Purification, Characterization, and Crystallization of the BTB/POZ Domain from the PLZF Oncoprotein

Abstract: The BTB/POZ domain defines a conserved region of about 120 residues and has been found in over 40 proteins to date. It is located predominantly at the N terminus of Zn-finger DNA-binding proteins, where it may function as a repression domain, and less frequently in actin-binding and poxvirus-encoded proteins, where it may function as a protein-protein interaction interface. A prototypic human BTB/POZ protein, PLZF (promyelocytic leukemia zinc finger) is fused to RAR␣ (retinoic acid receptor ␣) in a subset of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
42
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 32 publications
8
42
0
Order By: Relevance
“…Crystallographic analysis revealed that the POZ monomers interact via an extensive hydrophobic interface with interlocked ␣ helices and ␤ sheets, consistent with the observation that the domain is an obligate dimer (1,28). In addition, there is crystallographic evidence for higherorder associations between the BTB dimers through ␤-sheet interactions on the hydrophobic floor of the dimer (1,29).…”
supporting
confidence: 52%
“…Crystallographic analysis revealed that the POZ monomers interact via an extensive hydrophobic interface with interlocked ␣ helices and ␤ sheets, consistent with the observation that the domain is an obligate dimer (1,28). In addition, there is crystallographic evidence for higherorder associations between the BTB dimers through ␤-sheet interactions on the hydrophobic floor of the dimer (1,29).…”
supporting
confidence: 52%
“…Kelch superfamily proteins have diverse functions including regulating the actin cytoskeleton, gene expression, and protein ubiquitination. The BTB/POZ domain is a zinc finger and protein-protein interaction domain (Li et al, 1997) known to dimerize (e.g. (Cullen et al, 2004;Soltysik-Espanola et al, 1999).…”
Section: Krip6 Is a Btb/kelch Protein Interacting With Glur6mentioning
confidence: 99%
“…First, the POZ domain can mediate homomeric as well as heteromeric POZ-POZ interactions (Bardwell and Treisman, 1994;Dhordain et al, 1995;Seyfert et al, 1996). The PLZF POZ domain, which has been studied in more detail, forms a very stable homodimer (Li et al, 1997b). Second, the POZ domains of BCL-6, PLZF and ZF5 have been shown to mediate transcriptional repression Albagli et al, 1996;Chang et al, 1996;Seyfert et al, 1996;Kaplan and Calame, 1997;Li et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%